2013
DOI: 10.1093/heapol/czt064
|View full text |Cite
|
Sign up to set email alerts
|

The cost of injury and trauma care in low- and middle-income countries: a review of economic evidence

Abstract: There is a lack of injury-related economic evidence from LMICs. Current costing research has considerable variability in the costs and cost descriptions of injury and associated prevention interventions. The generalizability of these studies is limited. Yet the economic burden of injury is high, suggesting significant potential for cost savings through injury prevention. A standardized approach to economic evaluation of injury in LMICs is needed to further prioritize investing in injury prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 47 publications
3
115
0
Order By: Relevance
“…This study supports the finding that there continues to be a paucity of comprehensive costeffectiveness evidence to support the adoption and implementation of interventions in LMIC settings that have been shown to prevent injuries due to road traffic (Staton et al 2016;Wesson et al 2014). We have illustrated the need for further studies that explore outcomes specifically for children, young people and vulnerable road users.…”
Section: Implications For Public Health Practice Policy and Researchsupporting
confidence: 80%
See 2 more Smart Citations
“…This study supports the finding that there continues to be a paucity of comprehensive costeffectiveness evidence to support the adoption and implementation of interventions in LMIC settings that have been shown to prevent injuries due to road traffic (Staton et al 2016;Wesson et al 2014). We have illustrated the need for further studies that explore outcomes specifically for children, young people and vulnerable road users.…”
Section: Implications For Public Health Practice Policy and Researchsupporting
confidence: 80%
“…Wesson et al (2014) reported a systematic review of studies describing the economic burden of injury and trauma in LMICs. The review identified 68 studies meeting the inclusion criteria, of which 31 considered the economic burden of RTIs, although only six of these were full economic studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…For every injury death, there are 20-50 nonfatal injuries that result in some form of disability, impacting quality of life, productivity, and financial security (31,95).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, similar to this one [94,95], and later studies referring to this study [96][97][98][99] have not had the same study question as this study had. The overall picture that emerges is, however, in line with the findings in this study, namely: there is a dearth of evidence and that the methodological consistency between studies varies substantially, which calls for a more standardised approach to economic evaluation.…”
Section: Cost-effectiveness Of Injury Prevention (Study I)mentioning
confidence: 63%